Systemic lipid and glucose modulation differentially affects cognitive function and neuroinflammation in a mouse model of Alzheimer’s disease - Kynigopoulos, Demos; Fella, Eleni; Shahabian, Lucy; Christodoulou, Christiana C.; Papacharalampous, Revekka; Diskos, Konstantinos; Vagiaki, Lida Evmorfia; Sidiropoulou, Kyriaki; Pipis, Menelaos; Kleopa, Kleopas A.; Panayiotou, Elena (Frontiers in Neuroscience, 2025)
IntroductionAlzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by synaptic dysfunction and cognitive decline. Increasing evidence implicates systemic metabolic dysregulation in AD pathogenesis, yet it remains unclear whether modulation of peripheral lipid and glucose metabolism can alter disease progression.MethodsWe investigated the effects of two FDA-approved metabolic agents—Alirocumab, a PCSK9 inhibitor that lowers LDL cholesterol, and Gliclazide, a sulfonylurea that enhances insulin secretion—in male 5xFAD mice, a transgenic model of AD. Animals received chronic treatment for five months. Behavioral testing, hippocampal electrophysiology, ELISA, lipidomics, and adipokine profiling were performed to assess cognitive, synaptic, and molecular outcomes.ResultsAlirocumab significantly improved spatial working memory, restored hippocampal long-term potentiation, and normalized synaptophysin expression. Gliclazide reduced neuroinflammation and partially preserved glial and neuronal markers. Both treatments decreased amyloid burden and modulated adipokine levels, with Alirocumab elevating leptin and omentin in brain and serum. Lipidomic profiling of visceral adipose tissue revealed distinct lipid remodeling and highlighted candidate pathways linking systemic metabolism to central nervous system outcomes.DiscussionThese findings demonstrate that systemic modulation of lipid and glucose metabolism can influence neurodegenerative and synaptic processes in AD. The results support metabolic interventions as a potential strategy to modify AD progression through peripheral–central metabolic crosstalk.